Surface Clutter Reduction for Ground Penetrating Radar - Queen Hesti Ramadhamy; Erfansyah Ali; Aloysius Adya Pramudita (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Surface clutter is one of the problem in GPR survey that may caused the difficulty in detecting object. The rough of the ground surface caused the surface clutter is a method for reducing the clutter is need to improved the detection result. One of method is used to achieve that objective is averaging method. In this experiment, GPR system is modelled using VNA and the averaging method is resulting on target object detection which is recognized more clearly.